2019
DOI: 10.28982/josam.626480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microorganisms isolated from blood cultures and their susceptibility profiles to antibiotics in five years period

Abstract: How to cite / Atıf için: Arabacı Ç, Kutlu O. Evaluation of microorganisms isolated from blood cultures and their susceptibility profiles to antibiotics in five years period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
4
1
0
Order By: Relevance
“…The most common causative agent after CA was C.parapsilosis with 17.2%. This result was consistent with other studies conducted in Turkey [14][15][16][17]. In our study, the third most common strain was C. glabrata (13.4%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most common causative agent after CA was C.parapsilosis with 17.2%. This result was consistent with other studies conducted in Turkey [14][15][16][17]. In our study, the third most common strain was C. glabrata (13.4%).…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant correlation between the distribution of candida species among surgical and non-surgical patients. Aliskan et al reported similar results in their study [14]. Candidemia has been reported to be the cause of mortality at a rate of 30-60% [25,10].…”
Section: Discussionsupporting
confidence: 69%
“…In study conducted at academic medical centers in the United States between 2015 and 2019 showed most CRE were K. pneumoniae (63.2%), followed by E. coli (14.5%) concurrent to our study [18]. Similarly, Porwall et al identified the most common carbapenem resistant Gram negative isolate was CRKP (44%) followed by CREC (26%) [19].…”
Section: Discussionsupporting
confidence: 80%
“…In the national ARMOR surveillance study conducted in the USA, ciprofloxacin susceptibility was 94.9 % in 389 ocular P. aeruginosa strains [21]. Turkey-based studies have reported that susceptibility to ciprofloxacin was 51%-70% [12,22,23]. In this study, ciprofloxacin resistance (18.5%) was close to the empirical treatment limit (20%).…”
Section: Discussionsupporting
confidence: 53%